Arm function after stroke. An evaluation of grip strength as a measure of recovery and a prognostic indicator. Issue 11 (November 1989) - Sunderland, A; Tinson, D; Bradley, L; Hewer, R L
Abstract : The value of strength of voluntary grip as an indicator of recovery of arm function was assessed by testing 38 recent stroke patients using a sensitive electronic dynamometer, and comparing the results with those from five other arm movement and function tests (Motricity Index, Motor Club Assessment, Nine Hole Peg Test, and Frenchay Arm Test). This procedure allowed measurement of grip in a large proportion of patients, and strength correlated highly with performance on the other tests. Measuring grip over a six month follow up period was a sensitive method of charting intrinsic neurological recovery. The presence of voluntary grip at one month indicates that there will be some functional recovery at six months.